Women's Speech In A State of Anger: A Neuropragmatic Study - Rahmadani Sabrian; Gusdi Sastra; Ike Revita (Masyarakat Linguistik Indonesia Universitas Andalas, 2019)
This research aims to describe and to translate the emotional prosody patterns through Praat program and also to describe types of speech acts used by female characters in an emotional state in the film